Pathogenesis and Therapy of Oral Carcinogenesis - Tarle, Marko; Lukšić, Ivica (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We present our reprint dedicated to the study of oral squamous cell carcinoma (OSCC). Despite advances in diagnosis and treatment, OSCC remains a challenge for scientists and clinicians worldwide. This compilation of articles addresses novel biomarkers and therapeutic targets for the prevention and treatment of OSCC. Articles cover topics such as the combined use of pathway inhibitors in cancer control, the role of genes and microRNAs, the interaction between smoking and HPV infection, and potential biomarkers for diagnosis and therapy. These publications provide insights into the latest research and inspire further innovation.